The effect of increased uric acid levels on the severity of coronary artery stenosis based on SYNTAX score in patients with chronic coronary syndrome - Lestari, Defyna Dwi; Budi Satrijo; Mohamad Saifur Rohman (Universitas Brawijaya, 2026)
Background: Recent findings indicate that the adverse effects of uric acid (UA) on the coronary arteries contribute to the severity of atherosclerotic disease. Objective: This analysis investigates the relationship between serum uric acid concentrations and the SYNTAX score, quantifying coronary artery disease severity (CAD). Methods: A cross-sectional study took place at Saiful Anwar General Hospital from January 2022 to December 2024. A total of 1156 patients diagnosed with CAD who underwent coronary angiography were chosen for the study. Result: The analysis of uric acid levels led to the classification of participants into two distinct groups: the hyperuricemia group (n = 396) and the normouricemia group (n = 760). The analysis involved comparing the groups in terms of the occurrence of CAD and SYNTAX score while examining gender-specific quartiles of uric acid levels. The clinical baseline data underwent evaluation through suitable statistical methods, and a multivariate logistic regression analysis was conducted to pinpoint independent risk factors for CAD. Conclusion: UA showed a positive relationship with the SYNTAX score in individuals with CAD. It serves as an independent indicator for assessing the extent of coronary artery stenosis and has predictive capabilities.